MINERAL SUBSTANCES IN SUGAR BEET MOLASSES - Rada Jevtić Mučibabić; Jasna Grbić; Bojana Filipčev; Olivera Šimurina; Tatjana Kuljanin (Journal of Engineering & Processing Management, 2013)
Molasses, a byproduct of the sugar industry, presents multicomponent system of complex chemical composition and a suitable raw material for a range of food technology. The composition of molasses is conditioned by the sugar beet quality, applied beet processing technology and used aids. The main parts of molasses consists carbohydrates, primarily sucrose. Significant percentage of nonsucroses presents the compounds whose qualitative and quantitative composition is essential for estimation the benefits of molasses as a raw material in the processing and fermentation industries. Non sucrose molasses substances are divided into inorganic (mineral) compounds, organic compounds with nitrogen and organic compounds without nitrogen. The research work has dealt with ivestigations of molasses mineral substances, which was produced in the sugar beet processing of Serbian factories. The analysis included the impact of the processing conditions on content and composition of molasses nonsucrose substances.
Keywords: molasses; quality; mineral substances